Analysis of Work Factors on Employee Performance Mediated by Job Satisfaction in Manufacturing Company - Yuswardi, Yuswardi; Sentoso, Antony; Handayani, Annisya Mega Dwi (Universitas Islam Kadiri, 2024)
This research aims to determine the influence of the work environment, work motivation, rewards, and compensation on employee performance, as well as the mediating variableof job satisfaction. The method used in this research is a quantitative analysis method and a survey method by distributing questionnaires and producing 404 respondents from manufacturing companies in the city of Batam. This research was tested using the Smart Partial Least Squares (SmartPLS) model, namely a model that uses partial least squares based on partial and total probability. The results of this study show that the work environment has a significant effect on job satisfaction, work motivation has a significant effect on job satisfaction, awards have a significant effect on job satisfaction, compensation has a significant effect on job satisfaction, job satisfaction has a significant effect on the work environment, the work environment is mediated by job satisfaction has a significant effect on employee performance, work motivation mediated by job satisfaction has an effect on employee performance, rewards mediated by job satisfaction have an effect on employee performance, and compensation mediated by job satisfaction has a significant effect on employee performance. The results of this research are able to illustrate what factors can produce employees with high qualifications.